Examining the Obstacles to Broadening Participation in Computing: Evidence from a Survey of Professional Workers. - Ash, Ronald A.; Coder, Leanne; Dupont, Brandon; Rosenbloom, Joshua L. (Contemporary Economic Policy, 2009)
This article describes the results of a survey of professional workers that was designed to explore the underlying reasons for the widely documented underrepresentation of women in information technology (IT) jobs. Our analysis suggests that it is different occupational personalities between men and women rather than the demanding nature of IT work that is largely responsible for the relatively few women in IT occupations. We discuss the implications these results have for policies that are designed to create greater gender equity in the rapidly growing IT industries. (JEL J08, J24, J70) Reprinted by permission of the publisher.